Stability Analysis and Confidence Level Evaluation of Backfill Mining under High and Steep Rock Slopes - Bo-yi Hu; Xin-min Wang; Shuai Li; Jian-wen Zhao; Nyandwe Musonda Eugénie (Advances in Civil Engineering, 2018)
To extract the 6.3 million tons of high-quality phosphate resources, a stability analysis and confidence level evaluation of backfill mining under high and steep rock slopes (HSRS) were conducted using the Slide software and a Monte Carlo simulation. The geological model of HSRS was constructed based on a geotechnical investigation. A series of laboratory tests were conducted to obtain the engineering parameters of the rock mass, and the mechanism of action of the backfill mining method was analyzed. After the stability analysis, the average safety factors of HSRS for normal operation are 1.575 (backfill method) and 1.509 (open-stope method), and for seismic conditions, they are 1.470 (backfill method) and 1.380 (open-stope method). According to the confidence level evaluation, the average failure probability of HSRS by using the backfill mining method is 0.0143. The results showed that using the backfill mining method under HSRS had better seismic stability and lower potential levels of destruction than using the traditional open-stope mining method. In addition, the backfill mining method can prevent the development of a circular failure surface, reduce the destructive effect of mining to a minimum, and maintain the lower failure probability of HSRS.